(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Turbulence in the US economy has been increasing since 1930 as reflected in measurement of matrices such as revenue volatility, profitability and employment of publicly traded firms in United States (Sull,2009) Industry level turbulence has accelerated rapidly since 1990 as reflected in industry level measures such as concentration, performance gaps and shift in leadership positions. Data on IT spending during the same period indicates that this increase has coincided with massive increase in IT investment, therefore suggesting that IT has created a new economics of competitiveness (Mcafee and Brynjolfsson, 2008)Agility as a concept was first introduced in 1990s to deal with the emergent new competitive environment (Stanculescn, Niculae Grigore).Defined as an organization’s “ability to sense and respond to changes in an organization’s internal and external environment by quickly assembling resources, relationships and capabilities”(Gallaghe and Worrel, 2007), organizational agility is today viewed as a strategic imperativeIn this paper we explore the evolution of the concepts of organization agility which combines customer agility, strategic agility, operational agility and partnership agility, the role of Information technology in enabling agility and the mechanisms underlying the influence through a systematic literature review.For the purpose of this research we use Design Oriented Research Synthesis. Structured Literature Review (SLR) of relevant literature on Organizational Agility and IT Enabled Organizational Agility is conducted to extract the conceptual ontology of the current research and design prepositions identifying the Organizational Agility are formulated. These prepositions can form the basis of further empirical research.